The Influence of the Time Token Learning Model on Knowledge of Prevention Violence and Sexual Harassment in Early Adolescents - Dinda Briliani Putri; Tuti Sukini; Ribkha Itha Idhayanti (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
Violence and sexual harassment against young teenagers in Indonesia is a serious problem that often occurs. Referring to the DP3AKB data for Central Java Province from 2016 to 2021, itshows that the highest type of violence is sexual violence. Thisis due to the low level of knowledge about sex education to prevent violence and sexual harassment in early teens. One way to prevent sexual violence and harassment is to increase the knowledge of early adolescents. The time token learning model was chosen because it is a democratic learning model, increases student participation, and increases knowledge and social skills to explore, prevent and report sexual violence and harassment. The aim of this research is to determine the effect of the time token learning model on knowledge of preventing violence and sexual harassment in early adolescents. This type of quantitative research, the research method used is quasi-experimental (Quasy Experiment), with a one group pretest-posttest research design. The population is 51 respondents and the sampling technique is purposive sampling, the total sample is 50 respondents from grade 5 students at SDN 5 Kedungsari, Magelang City. Research data were analyzed using the Wilcoxon Signed Ranks test with an alpha of 5%. The results of the research show that there is a significant influence of the time token learning model on knowledge of preventing violence and sexual harassment in early adolescents with the Wilcoxon statistical test results from Z calculated knowledge of -6.116 with a p value = 0.000 <0.05.